Modeling Ground Waters Dynamics and Pollution - Biliaiev, Mykola M.; Kozachyna, Valeriia V. (Prydniprovs'ka State Academy of Civil Engineering and Architecture, Dnipro, Ukraine, 2024)
ENG: Problem statement. Large accumulators of liquid waste (e.g., mine water ponds, tailing ponds, etc.) are long-term sources that change the hydrological regime. A negative consequence of this process is flooding of the territory. In addition, the infiltration of contaminated water from such hazardous sources changes the quality of groundwater. Therefore, it is important to analyze the impact of such anthropogenic sources on the process of flooding and deterioration of groundwater quality. To solve this problem, it is very important to use the method of mathematical modeling as an effective mean of researching problems of this class, since the use of physical modeling is practically impossible within the scope of problems of this class. The purpose of the article. Development of numerical models for predicting changes in the hydrological regime (flooding of the territory) and groundwater quality under the influence of anthropogenic pollution sources. Methodology. To assess the dynamics of changes in the hydrological regime, a two-dimensional equation of filtration of a non-pressure groundwater flow is used. A two-dimensional geomigration equation (planned model) is used to analyze changes in groundwater quality during infiltration of contaminated water from the settling pond. This equation takes into account the convective transfer of contaminants in the filtration flow, dispersion, and the intensity of contaminant infiltration into the groundwater flow. The method of total approximation is used for numerical integration of the filtration equation. For the numerical integration of the geomigration equation, an implicit splitting scheme is used. Scientific novelty. Effective numerical models for rapid assessment of changes in groundwater dynamics and quality under the influence of anthropogenic sources that change the hydrological regime are proposed. The constructed numerical models take into account a set of important physical factors that affect the process of geomigration and flooding of the territory, namely: filtration coefficient, variable depth of free-flowing groundwater, dispersion, intensity of the source of impurity emission into the groundwater flow. This makes it possible to obtain a comprehensive assessment of the process of flooding and groundwater pollution.. Practical significance. A computer code has been created that allows practical usage of the developed numerical models. This code is an effective tool for theoretical study of non-stationary processes of territory flooding and anthropogenic groundwater pollution. Conclusions. A numerical model for calculating groundwater dynamics has been developed. The model allows to predict the level of groundwater rise under the influence of a man-made source of wastewater infiltration from a settling pond. A numerical model for calculating the process of geomigration from an anthropogenic source of emissions has been developed. The model makes it possible to predict the dynamics of contamination zone formation in a non-pressure groundwater flow. The developed numerical models take into account the most important parameters that affect the formation of flooding zones and groundwater contamination.

UKR: Постановка проблеми. Великі накопичувачі рідких відходів (наприклад, шахтні водойми, хвостосховища тощо) – це довготривалі джерела, що змінюють гідрологічний режим. Негативним наслідком цього процесу стає підтоплення території. Крім того, проникнення забрудненої води з таких небезпечних джерел змінює якість ґрунтових вод. Тому актуальним бачиться аналіз впливу таких антропогенних джерел на процес підтоплення та погіршення якості підземних вод. Для розв’язання цієї задачі дуже важливе застосування методу математичного моделювання як ефективного засобу дослідження задач цього класу, оскільки застосування фізичного моделювання в рамках задач цього класу практично неможливе. Мета роботи – розроблення чисельних моделей для прогнозування зміни гідрологічного режиму (підтоплення території) та якості підземних вод за впливу джерел антропогенного забруднення. Методика. Для оцінення динаміки змін гідрологічного режиму використовується двовимірне рівняння фільтрації безнапірного стоку підземних вод. Двовимірне рівняння геоміграції (планова модель) використовується для аналізу змін якості ґрунтових вод під час інфільтрації забрудненої води з відстійника. Це рівняння враховує конвективний перенос забруднень у фільтраційному потоці, дисперсію та інтенсивність інфільтрації забруднювачів у потік ґрунтових вод. Для числового інтегрування рівняння фільтрації застосовується метод повної апроксимації. Для чисельного інтегрування рівняння геоміграції використовується неявна схема розщеплення. Наукова новизна. Запропоновано ефективні числові моделі для експрес-оцінки змін динаміки та якості підземних вод за впливу антропогенних джерел, що змінюють гідрологічний режим. Побудовані чисельні моделі враховують комплекс важливих фізичних факторів, що впливають на процес геоміграції та затоплення території, а саме: коефіцієнт фільтрації, змінну глибину залягання безнапірних підземних вод, дисперсність, інтенсивність джерела викиду домішок у підземні води, потік. Це дає можливість отримати комплексну оцінку процесу підтоплення та забруднення підземних вод. Практична значимість. Створено комп’ютерний код, який дозволяє практично використовувати розроблені числові моделі. Цей код – ефективний інструмент для теоретичного дослідження нестаціонарних процесів підтоплення території та антропогенного забруднення підземних вод. Висновки. Розроблено чисельну модель для розрахунку динаміки підземних вод. Модель дозволяє прогнозувати рівень підняття ґрунтових вод за впливу техногенного джерела інфільтрації стічних вод із відстійника. Розроблено числову модель для розрахунку процесу геоміграції від антропогенного джерела викидів. Модель дає змогу прогнозувати динаміку формування зони забруднення в безнапірному стоці ґрунтових вод. Розроблені числові моделі враховують найважливіші параметри, що впливають на формування зон затоплення та забруднення ґрунтових вод.
Моделювання динаміки грунтових вод та їх забруднення
M. Biliaiev: ORCID 0000-0002-1531-7882; Val. Kozachyna: ORCID 0000-0002-7433-7306
Keywords: ground waters dynamics; ground waters pollution; territory flooding; mass transfer; mathematical modeling; динаміка підземних вод; забруднення підземних вод; затоплення території; масоперенос; математичне моделювання; КГВФ; TECHNOLOGY::Other technology::Environmental engineering